Budaya Literasi - Hermanto Hermanto (LPPM IAIN Sorong, 2019)
Literacy is something that has received serious attention in recent years in Indonesia. This is because the results of the 2015 Program for International Student Assessment (PISA) study on students 'reading ability stated that students' reading skills in ndonesia ranked 69th out of 76 countries surveyed. This data is reinforced by the World's Most Literate Nations data, compiled by Central Connecticut State University in 2016, our literacy ranking is in the second lowest position of 61 countries studied. Indonesia is simply better than Bostwana, a country in the southern region of Africa. With this, the role of various parties is demanded, including universities in developing literacy in Indonesia. STAIN Sorong is one of the universities in the Eastern region of Indonesia.